A study on the effect of CBSM-based psychological intervention on self-management ability and quality of life in colorectal cancer patients from the perspective of benefit finding: A quasi-experimental study - Linzhi Jiang; Zhouyuan Peng; Rongrong Liu; Lei Chen; Yang Wu; Xingqun Tan; Fan Wang; Liyuan Sun (PLoS ONE, 2026)
Background Colorectal cancer (CRC) is a highly prevalent malignant tumor in China. Patients often experience negative emotions due to disease- and treatment-related stress, which impairs their ability to self-manage the illness. Benefit finding (BF) can improve patients’quality of life through cognitive restructuring. Cognitive Behavioral Stress Management (CBSM) has been proven to exert positive intervention effects on breast cancer patients, but relevant research on its application in Chinese CRC patients and its impact on their BF, quality of life and self-management ability remains scarce. Objectives The study aimed at evaluating the effectiveness of the intervention programme based on CBSM model on benefit finding, self-management ability, and quality of life among postoperative CRC patients. Methods A single-center, non-randomized controlled trial (non-RCT) time series study was conducted among 72 CRC patients. They were divided into an intervention group (n = 36) and a control group (n = 36). The Benefit Finding Scale (BFS), Cancer Patient Self-management Assessment Scale (CPSAS), and Cancer Rehabilitation Evaluation System-Short Form (CARES-SF) scales were used to assess BF level, self-management ability, and quality of life, respectively. The control group received routine care, while the intervention group received an 8-week CBSM-based psychological intervention in addition to routine care. Baseline data were collected before the intervention, and post-test assessments were carried out at 1 and 3 months after the intervention. Results Of the 72 enrolled postoperative CRC patients, 67 (93.1%) completed the study, with an overall dropout rate of 6.94%. At 1 month (T1) and 3 months (T2) post-intervention, the intervention group had significantly higher total BF scores than the control group (T1: P = 0.001, Cohen’s d = 0.57; T2: P < 0.001, Cohen’s d = 0.63). Total CPSAS scores in the intervention group were significantly higher than those in the control group at T1 and T2 (T1: P = 0.007, Cohen’s d = 0.48; T2: P < 0.001, Cohen’s d = 0.66), though no significant between-group differences were observed in the dimensions of communication with medical staff and information management (all P > 0.05). While total CARES-SF scores (indicating fewer health-related issues when lower) in the intervention group were lower than those in the control group at T1 and T2, no statistically significant between-group differences were found (all P > 0.05). Correlation analyses in the intervention group showed a possible positive correlation between BF and self-management ability scores at T0, T1, and T2 (r = 0.706, 0.689, 0.551; all P < 0.001). BF scores were negatively correlated with CARES-SF scores at T0 and T2 (r = −0.295, −0.449; all P < 0.05). Self-management ability scores were negatively correlated with CARES-SF scores at T1 (r = −0.525, P < 0.05). Conclusion CBSM-based psychological intervention can effectively enhance BF levels, promote self-management ability, and improve health-related issues in postoperative CRC patients. Moreover, a mutually reinforcing and synergistic relationship exists among these three dimensions. Trial registration ClinicalTrials.gov ChiCTR2400092570